2018
DOI: 10.1136/flgastro-2018-101007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a European-wide survey on paediatric endoscopy training

Abstract: ObjectiveTo evaluate quality of paediatric endoscopy training of Young members of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN).MethodsAn online questionnaire designed by the Young ESPGHAN Committee was sent to 125 Young ESPGHAN members between February 2014 and September 2015. The questionnaire comprised 32 questions addressing some general information of the participants and the structure of their paediatric gastroenterology, hepatology and nutrition programmes; pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The availability of structured direct observation tools such as Gastrointestinal Endoscopy Competency Assessment Tool for pediatric colonoscopy (GiECATkids) is important to provide a framework for teaching, support trainee learning through instructive feedback, assess trainee progress toward specific competency-based milestones, facilitate identification of skill deficits and ensure readiness for independent practice 34 . Despite the widely acknowledged need for a structured training program in pediatric endoscopy, there is wide variation across Europe in the opportunities for and quality of endoscopic training, as demonstrated by the earlier ESPGHAN survey of trainees 13 and this more comprehensive Europe-wide survey of training centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of structured direct observation tools such as Gastrointestinal Endoscopy Competency Assessment Tool for pediatric colonoscopy (GiECATkids) is important to provide a framework for teaching, support trainee learning through instructive feedback, assess trainee progress toward specific competency-based milestones, facilitate identification of skill deficits and ensure readiness for independent practice 34 . Despite the widely acknowledged need for a structured training program in pediatric endoscopy, there is wide variation across Europe in the opportunities for and quality of endoscopic training, as demonstrated by the earlier ESPGHAN survey of trainees 13 and this more comprehensive Europe-wide survey of training centers.…”
Section: Discussionmentioning
confidence: 99%
“…The ESPGHAN and North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) Guidelines for training in Pediatric Gastroenterology define appropriate training and the minimum number of procedures recommended to achieve competency in endoscopy, and emphasize the need for trainees to become familiar with endoscopic procedures and understand their use, interpretation and limitations [2,9]. However, a recent European survey found that training in pediatric endoscopy in Europe is variable and often inadequate, as reported by trainees themselves [13].…”
Section: Introductionmentioning
confidence: 99%
“…A UK web-based survey with eight questions regarding diathermy practice for colonic polypectomy had a 71.8% response rate [25]. A further European wide web-based survey contained 32 questions regarding the structure of training programmes on paediatric endoscopy [26]. This survey was also sent via a professional society (Young ESPGHAN) and had a response rate of 62% [26].…”
Section: Limitationsmentioning
confidence: 99%
“…A further European wide web-based survey contained 32 questions regarding the structure of training programmes on paediatric endoscopy [26]. This survey was also sent via a professional society (Young ESPGHAN) and had a response rate of 62% [26]. It appears that the main differences between the administration of these surveys and our current survey were the length of time the survey was open and the number of reminders sent.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation